Factors related to methamphetamine relapse risk among clients in the substance rehabilitation center of National Narcotics Board in West Java, Indonesia - Gian Nurmaindah Hendianti; Penpaktr Uthis (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - This purpose of this paper is to describe methamphetamine relapse risk, examine the relationship between factors in the dynamic model of relapse and methamphetamine relapse risk. Design/methodology/approach - A total of 165 clients from the Substance Rehabilitation Center of National Narcotics Board in West Java, Indonesia were recruited. The research instruments included a demographic characteristic questionnaire and eight different tests: Drug Taking Confidence Questionnaire; Stimulant Effect Expectancy Questionnaire; Stage of Change Readiness and Treatment Eagerness Scale version 8.0 for Drug; Coping Strategies Inventory Short Form; Positive Affect and Negative Affect Schedule; Desire for Speed Questionnaire; Social Support Questionnaire; and the Stimulant Relapse Risk Scale. Descriptive statistics were used to analyze the data. Pearson's product moment correlation was used to test the relationship among variables. Findings - Clients (63 percent) were at a moderate level of methamphetamine relapse risk (mean=56.33, SD=10.54). Outcome expectancy, positive emotional state, negative emotional state and craving were positive and had a significant correlation with relapse risk (r=0.261, r=0.380, r=0.370, r=0.509, p<0.01, respectively). Self-efficacy was negative and had a significant correlation with relapse risk (r=−0.316, p<0.01). Motivation, coping and social support had no correlation with relapse risk. Originality/value - Two-thirds of the clients in a rehabilitation center have a tendency to relapse following treatment. Nursing intervention for early detection of methamphetamine relapse risk during treatment by using standardized instruments should be implemented.